Upaya Menurunkan Waktu Tunggu Obat Pasien Rawat Jalan dengan Analisis Lean Hospital di Instalasi Farmasi Rawat Jalan RS Atma Jaya - Suryana, Danyel (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
One option to increase efficiency, service quality and patient safety in the United States of America is by using the Lean Thinking concept, which are implemented in Hospitals to become a Lean Hospital. In Atma Jaya Hospital, a class B study private hospital, the research analyses the workflow of prescription sevice in outpatient pharmacy departement to act as data for improvement analysis. Also, by utilizing Root Cause Analysis (RCA), operational research methology, in-depth observation and interviews are conducted at compounding and non-compounding medicine storage of Outpatient Patient Departement, the result shows non-value added activities reaches 85%, while value added activities are only 15% on non-compounding medicine storage. While, on compounding medicine storage, non-value added and value added activities are at 68% and 32% respectively. These data clearly shows that great inefficiencies has occurred. Solution is suggested to increase the efficiency in the department, changing Hospital Information System and activate the Quality Control Team function. If these steps are implemented, we can expect the overall efficiency in the Outpatient Pharmacy Departement to improve significantly and resulted in higher patient satisfaction